‘Des nouvelles de mon infortunée sœur’: Marie-Antoinette dans les lettres de l’archiduchesse Marie-Christine à l’empereur François - Catriona Seth (Modern Languages Open)
The correspondence between Archduchess Maria-Christina of Austria (1742–1798) – Marie-Antoinette’s elder sister and wife of Albert, duke of Saxony-Teschen (1738–1822) – and her nephew Francis II (1768–1835) sheds new light on the last queen of France’s final months, as well as on the Habsburgs’ attitude towards her and her legacy. The difficulty of obtaining accurate information and the whirl of various rumours about the fate of the illustrious prisoner and her close family combined with the foreign powers’ evident reluctance to intervene for fear of political and military repercussions. Not only were the Austrian Netherlands (of which the duke and duchess of Saxony-Teschen were governers) at boiling point, war had also been declared between Marie-Antoinette’s homeland and the country where she hoped her son the dauphin would one day reign. Although never particularly close to her youngest sister, Maria-Christina was caught off-guard by the rush of events. Her letters, written with ever greater frequency at particularly critical moments, betray, alongside rare moments of optimism, a profound feeling of impotence, which was echoed by a kind of resignation from the Holy Roman emperor. Francis II – the successor to Leopold II, who died suddenly on 1 March 1792 – never met his relative who languished at the Temple and at the Conciergerie before mounting the scaffold. These documents allow us to propose a periodisation whose key moments nuance certain historiographical accounts of the revolutionary era. Résumé Les échanges entre l’archiduchesse Marie-Christine d’Autriche (1742–1798), sœur aînée de Marie-Antoinette et épouse d’Albert de Saxe-Teschen (1738–1822), et son neveu François II (1768–1835) entre 1792 et 1794 offrent un éclairage inédit sur les derniers mois de la ci-devant reine de France et l’attitude des Habsbourg à son égard et face à son héritage. La difficulté d’obtenir des renseignements fiables, la circulation de rumeurs diverses sur le sort de l’illustre prisonnière et des siens se conjuguent, pour les puissances étrangères, avec des réticences palpables à intervenir par crainte des retombées politiques et militaires alors même que les Pays-Bas autrichiens, dont le duc et la duchesse de Saxe-Teschen sont gouverneurs, sont en ébullition et que la guerre est déclarée entre le pays de naissance de Marie-Antoinette et celui sur lequel elle espère voir régner un jour son fils, le dauphin. Si elle n’a jamais été particulièrement liée avec sa cadette, Marie-Christine est prise de court par la précipitation des événements. Sa correspondance, intensifiée dans son rythme lors de moments particulièrement critiques, laisse entendre, au détour de rares moments d’optimisme, un fort sentiment d’impuissance auquel répond une forme de résignation de l’empereur des Romains. François II, qui succède à son père Léopold II, mort subitement le 1er mars 1792, n’a jamais rencontré celle qui languit au Temple puis à la Conciergerie avant de monter à l’échafaud. Parmi les apports de ces documents, il y a la mise en place d’une périodisation dont les temps forts infléchissent certaines lectures historiographiques de l’époque révolutionnaire.